Nilai-Nilai Pendidikan Karakter dalam Novel Merindu Cahaya De Amstel - Nova Diana (Yayasan Darusssalam Bengkulu, 2025)
Character has a crucial role in maintaining the existence of a nation in the eyes of the world. Even though efforts have been made to instill the values of character education, the hope that young students from among students have good emotional intelligence is actually broken by deviant phenomena that still often occur. Responding that more efforts are needed beyond formal education in instilling character education values, this progressive era has paved the way for students to easily recognize and absorb character education values from various media. Novel is part of literature which also aims to educate people's lives. One novel that contains character education values and is considered to have a positive impact on instilling character values among adolescents is the novel Merindu Cahaya de Amstel by Arumi Ekowati. This type of research is library research (library research). The data collection technique that the authors use in this study uses the documentation method. The results of this study indicate that in the novel Merindu Cahaya de Amstel there are values of character education including religious values, fond of reading, independence, hard work, creativity, and tolerance. The relevance of character education values in the lives of today's youth can be found in family, school and community life.